Factors Influencing English Language Teachers' Motivation at Universities - Abdul Sahib, Shahla Mohsin Abdul Sahib (Thi Qar Arts Journal, 2021)
The speaking of  the English as a foreign language  has  expanded remarkably and consequently  the demands for  learning  the foreign language has expanded also   .These demands correlate with the motivation to learn the   foreign language .The teacher  is responsible of  the process of higher   education ;therefore he might be encouraged and supported .The teacher  is the person who transforms the principles of higher education     into practical steps   and convey them to students  in the classroom .The teacher's  encouragement  helps to enhance students' performance and then help students in improving their educational level  . Human's behavior is dominated by the reinforcement principle .People always  feel  happy when they achieve success and feel  sad when they  fail   . Identifying the motivation is not an easy task , because human behavior  is a very complex one . Knowing the kind  and the degree  of  encouragement  that suit the English language teachers will be of use for  those teachers  ,the student and the second language achievement .            The main focus of the study will be on identifying the  level of support  of the English language teachers and the  variables  that affect that support .